Isolation of peroxisomes from rat liver and cultured hepatoma cells by density gradient centrifugation - Manner, Andreas; Islinger, Markus (Peroxisomes, 2017)
Subcellular fractionation is still a valuable technique to unravel organelle-specific proteomes, validate the location of uncharacterized proteins, or to functionally analyze import and metabolism in individual subcellular compartments. In this respect, density gradient centrifugation still represents a very classic, indispensable technique to isolate and analyze peroxisomes. Here, we present two independent protocols for the purification of peroxisomes from either liver tissue or the HepG2 hepatoma cell line. While the former permits the isolation of highly pure peroxisomes suitable for, e.g., subcellular proteomics experiments, the latter protocol yields peroxisomal fractions from considerably less purity but allows to easily modify metabolic conditions in the culture medium or to genetically manipulate the peroxisomal compartment. In this respect, both purification methods represent alternative tools to be applied in experiments investigating peroxisome physiology.
Gesehen am 17.09.2018